The Influence of Raft Thickness on Settlement and Bending Moment of Pile Raft Foundation in Clay Soil - Anggraini, Nita; Sarifah, Fitriana (CIVED, 2024)
Geotechnical engineers often deal with shallow foundation designs to support relatively simple building structures. However, as the demand for construction grows over time, there is a need for larger and more complex building structures. This is closely related to the weight of the building that will be supported by the foundation as a substructure. Therefore, the development of knowledge about other types of foundations to support the structural loads above them is highly necessary. Pile foundations are a fairly good solution for supporting larger structural loads that cause significant settlement. In designing pile foundations as a structure, there will certainly be raft to combine each pile foundation into a unified group. Raft are often designed only for combining each pile, but in reality, It also provides additional influence on the foundation system besides just serving as pile heads and load distributors to the foundation system. The study will investigate the influence of raft thickness on settlement that occurs in piled raft foundations. The raft thickness varies, namely 0.25m; 0.40m; 0.80m; 1.50m; and 3.00m. The piled raft foundation will be modeled and analyzed using finite element program. This study shows that the raft thickness affects the differential settlement that occurs in the piled raft foundation system. The results indicate that the differential settlement can be addressed by designing the raft thickness.